A low cost lpg/gasoline dual fueling system for small displacement automotive engines - Lira Cacho, Guillermo (2005)
This article presents aspects related to the design and calculation of a new LPG supply system for small spark-ignition automotive engines, with carburetor, liquid-cooled, of up to 800 cm' displacement using the vapor phase of LPG. This new proposed system is characterized by its constructive simplicity, safety and its relative low cost, which allows economical, reliable work and low toxic emissions from the engine. The calculations of the regulator-osifier are shown, and for the design of the air/gas mixer, which is installed in series with the engine carburetor so that it can work in a dual way. A peculiar aspect of this system is the presence of a small heat exchanger that uses the hot water from the engine cooling system to compensate for the cooling of the LPG vapor, due to the Joule-Thompson effect, as the LPG pressure is reduced through of the system, and thus avoid eventual obstructions. Also, some experimental results of field tests are presented, showing comparatively the fuel economy.